Systemic ATTR-amyloidosis, a Rare Form of Internal Organ Damage - V. V. Rameev; R. P. Myasnikov; P. P. Vinogradov; L. V. Kozlovskaya; S. V. Moiseev; E. I. Fomicheva; S. A. Beregovskaya; E. A. Mershina; S. A. Kostina; L. A. Strizhakov; A. S. Rameeva; P. P. Tao; et al. (Рациональная фармакотерапия в кардиологии)
The article presents the case report of a rare hereditary form of systemic ATTR-amyloidosis in Russian patient with a discussion of approaches to the diagnosis and treatment of this form, also based on the own experience in the management of such patients. Modern ideas about the pathogenesis of the disease as well as detailed information about the clinical manifestations of amyloid cardiopathy and of other organs are presented. The nature of structural and hemodynamic changes in the heart is discussed on the basis of experience, including own, ultrasound examination of the heart in patients with amyloidosis, especially the article focuses the reader's attention on the true infiltrative nature of transtiretin amyloid cardiopathy in contrast to AL-amyloidosis, in which there is a significant inflammatory component that determines a more unfavorable natural course of AL-amyloidosis of the heart. The article discusses the differential diagnosis of different types of amyloidosis, the diagnostic difficulties associated with weak congophilia of transtiretin amyloidosis and at the same time substantiates the need for morphological verification of the diagnosis. Modern methods of treatment of ATTR-amyloidosis are discussed.